Preparation method and application of core-shell structure MOF material selectively adsorbing rhenium and rhenium adsorption material

By preparing core-shell MOF materials that selectively adsorb rhenium, the problem of rhenium resource waste in copper smelting waste acid was solved, and efficient selective adsorption and recovery of rhenium ions were achieved, which is suitable for industrial applications.

CN120939919BActive Publication Date: 2026-01-23CHINALCO ENVIRONMENTAL PROTECTION & ENERGY CONSERVATION GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511492205.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-23
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

Existing technologies for recovering rhenium from waste acid in copper smelting have problems such as wasting rhenium resources and increasing hazardous waste residue. Furthermore, existing methods are insufficient in selectively adsorbing rhenium ions, making it difficult to achieve efficient recovery.

Method used

A core-shell MOF material for selectively adsorbing rhenium is used, with UiO-66-SO3H as the core and SiO2 as the shell, combined with polyethyleneimine grafting to form pore sieving and electrostatic sieving, to achieve selective adsorption of rhenium ions. The strong coordination bond between Zr4+ nodes and rhenium ions and the ion exchange sites of sulfonic acid groups are used to achieve efficient adsorption.

Benefits of technology

It achieves highly efficient and selective adsorption of rhenium ions, avoiding the adsorption of sulfate, molybdate, and arsenate ions, thus improving the rhenium recovery efficiency and making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to copper smelting technical field, especially to selective adsorption rhenium's core-shell structure MOF material and rhenium adsorption material's preparation method and application, the present application provides a kind of selective adsorption rhenium's core-shell structure MOF material preparation method, including the following steps: (1) UiO-66-SO3H and template agent solution are mixed, dispersion is carried out, and dispersion liquid is obtained;(2) the dispersion liquid is mixed with ammonia water, then dropwise addition of silicate is hydrolyzed condensation reaction, and SiO2 coated UiO-66-SO3H, recorded as UiO-66-SO3H@SiO2;(3) the UiO-66-SO3H@SiO2 is dispersed in polyethyleneimine solution, and grafting reaction is carried out, and core-shell structure MOF material, recorded as UiO-66-SO3H@SiO2-PEI is obtained.The core-shell structure MOF material obtained by the preparation method of the present application can selectively adsorb rhenium anion, and when it is prepared into rhenium adsorption material, the industrial application of the adsorption material can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of copper smelting, in particular to a core-shell structure MOF material for selectively adsorbing rhenium and a preparation method and application of a rhenium adsorption material. BACKGROUND

[0002] Rhenium is a rare element that is rarer than rare earth elements, often associated with copper and molybdenum, and enters copper smelting waste acid along with copper smelting flue gas. The treatment of copper smelting waste acid in the industry is mostly harmless disposal, and little attention is paid to rhenium elements. Rhenium eventually enters the landfill along with arsenic sulfide slag, which not only wastes rhenium resources, but also increases the production of hazardous waste slag.

[0003] Currently, researchers have begun to focus on how to recover rhenium from copper smelting waste acid. Patent CN117682561A uses a multi-stage extraction method to treat rhenium-containing stripping solution, achieving purification and recovery of ammonium rhenate. However, the extractant is prone to emulsification to produce a third phase at low background concentration. Patent CN116715274A uses sodium thiosulfate to selectively precipitate rhenium, and then goes through a series of processes such as leaching, hydrolysis, acidification and extraction to recover 4N grade ammonium rhenate. Although the overall process achieves good results, heating is required during the precipitation of sodium thiosulfate and rhenium, which may release SO2, and the patent does not explicitly mention a gas collection device. In addition, sodium thiosulfate can also generate a precipitate with Cu 2+ Patent CN110468277A uses a neutralization-oxidation-resin adsorption technical route to recover rhenium from copper smelting waste acid. However, conventional anion resins have weak selectivity for molybdate, rhenate and sulfate ions, and there may be strong ion competition. Therefore, how to selectively adsorb rhenate and achieve a simple rhenium recovery process is a problem that needs to be solved in the field. SUMMARY

[0004] The present application provides a preparation method and application of a core-shell structure MOF material for selectively adsorbing rhenium, and the core-shell structure MOF material obtained by the preparation method can selectively adsorb rhenate, and the rhenium adsorption material prepared therefrom can realize industrial application of the adsorption material.

[0005] The present application provides a preparation method of a core-shell structure MOF material for selectively adsorbing rhenium, comprising the following steps:

[0006] (1) mixing UiO-66-SO3H and a template solution, dispersing to obtain a dispersion liquid,

[0007] (2) mixing the dispersion liquid with ammonia water, then adding silicate dropwise to carry out hydrolysis and condensation reaction to obtain UiO-66-SO3H coated with SiO2, denoted as UiO-66-SO3H@SiO2,

[0008] (3) dispersing the UiO-66-SO3H@SiO2 in a polyethyleneimine solution to perform a grafting reaction, to obtain a core-shell structure MOF material, denoted as UiO-66-SO3H@SiO2-PEI.

[0009] Optionally, the UiO-66-SO3H is prepared by a method comprising the following steps:

[0010] mixing a zirconium source, a sulfonic acid functionalized ligand, N,N-dimethylformamide and an acid, ultrasonicating for 8-20 min, then performing a solvothermal reaction, and performing solid-liquid separation on the obtained reaction liquid to obtain a UiO-66-SO3H precursor,

[0011] washing the UiO-66-SO3H precursor with N,N-dimethylformamide, ethanol and water in sequence, and drying to obtain the UiO-66-SO3H.

[0012] Optionally, the zirconium source is at least one of ZrCl4, ZrOCl4 and Zr(NO3)4, the sulfonic acid functionalized ligand is at least one of 2-sulfonic acid terephthalic acid and 2-sulfonic acid sodium terephthalate, and the acid is at least one of glacial acetic acid, formic acid and benzoic acid,

[0013] the molar ratio of the zirconium source and the sulfonic acid functionalized ligand is 1:0.8-1.2, the ratio of the zirconium source and N,N-dimethylformamide is 1 mmol: 45-55 mL, and the ratio of the N,N-dimethylformamide and the acid is 50 mL:0.17-0.23 mL,

[0014] the solvothermal reaction is performed at 115-125°C for 22-26 h,

[0015] the temperature of the N,N-dimethylformamide, ethanol and water used for washing is 50-60°C,

[0016] the drying is freeze-drying.

[0017] Optionally, the template agent in the template agent solution is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and octadecyltrimethylammonium bromide, the solvent in the template agent solution is ethanol, the concentration of the template agent solution is 0.25-0.35 mol / L, and the ratio of the UiO-66-SO3H and the template agent solution is 100 mg:45-60 mL,

[0018] the concentration of the ammonia water is 0.4-0.7 wt%, and the ratio of the UiO-66-SO3H and the ammonia water is 100 mg:0.15-0.3 mL.

[0019] The silicate is tetraethyl orthosilicate, and the ratio of the UiO-66-SO3H to the silicate is 100 mg: 0.08-0.12 mL,

[0020] The temperature of the hydrolytic condensation reaction is 10-20℃, and the time is 22-26 h, and the hydrolytic condensation process is kept in a stirring state.

[0021] Optionally, after the hydrolytic condensation reaction is completed, the obtained reaction liquid is subjected to solid-liquid separation to obtain a UiO-66-SO3H@SiO2 crude product, and the UiO-66-SO3H@SiO2 crude product is sequentially washed with a 1 wt% hydrochloric acid / ethanol solution and a 0.1 M sodium bicarbonate aqueous solution to obtain the UiO-66-SO3H@SiO2.

[0022] Optionally, the solvent of the polyethyleneimine solution is ethanol, the concentration of the polyethyleneimine solution is 1.5-2.5 wt / v%, the mass ratio of the polyethyleneimine in the polyethyleneimine solution to the silicon in the silicate is 3:6-8, and the molecular weight of the polyethyleneimine is 600-1600,

[0023] The grafting reaction is carried out under reflux conditions, the temperature of the grafting reaction is 65-75℃, and the time of the grafting reaction is 3.5-4.5 h.

[0024] Optionally, after the grafting reaction is completed, the reaction liquid obtained by the grafting reaction is subjected to solid-liquid separation to obtain a UiO-66-SO3H@SiO2-PEI crude product, and the UiO-66-SO3H@SiO2-PEI crude product is sequentially washed with ethanol, replaced with a tert-butyl alcohol solvent, and dried to obtain the UiO-66-SO3H@SiO2-PEI.

[0025] The application further provides a preparation method of a rhenium adsorption material.

[0026] The selective rhenium adsorption core-shell structure MOF material obtained by the preparation method in any one of the above technical solutions, polyvinylidene fluoride, and an organic solvent are mixed to obtain an extrusion material,

[0027] The extrusion material is extruded and then cut to obtain a rhenium adsorption material precursor,

[0028] The rhenium adsorption material precursor is dried after ethanol replacement to obtain the rhenium adsorption material.

[0029] Optionally, the mass ratio of the MOF material with core-shell structure selectively adsorbing rhenium and polyvinylidene fluoride is 1:0.4-0.6, and the ratio of the MOF material with core-shell structure selectively adsorbing rhenium and the organic solvent is 3.0 g: 6-8 mL,

[0030] The organic solvent is N-methyl pyrrolidone,

[0031] The precursor of the rhenium adsorption material is a columnar particle with a diameter of 1.5-2.5 mm and a length of 2-4 mm.

[0032] Optionally, the ethanol replacement includes the following steps: soaking the precursor of the rhenium adsorption material in a mixed solution of ethanol and N-methyl pyrrolidone with a volume ratio of 3:7 for 0.8-1.2 h, then soaking in a 60 v / v% ethanol aqueous solution for 0.8-1.2 h, and then soaking in ethanol for 0.8-1.2 h.

[0033] The application also provides a use of the rhenium adsorption material prepared by the preparation method in any one of the above technical solutions in recovering rhenium from waste acid.

[0034] Compared with the prior art, the application has the following beneficial effects:

[0035] The MOF material with core-shell structure selectively adsorbing rhenium prepared by the preparation method provided by the application takes UiO-66-SO3H as a core, takes SiO2 grafted with polyethylene imine as a shell layer with a pore structure, and realizes selective adsorption of rhenium acid radicals through pore size screening (to avoid adsorption of sulfate radicals, molybdate radicals and arsenate radicals) and electrostatic screening (to avoid adsorption of sulfate radicals and molybdate radicals). Specifically, when the waste acid solution passes through the surface of the MOF material with core-shell structure, ions and polymer ions with a hydration diameter larger than the pore diameter of the shell layer are blocked outside, the amino groups of PEI preferentially adsorb rhenium acid radicals with low charge density through the Donnan effect, and the rhenium acid radicals are enriched in the shell layer pores, Zr 4+ The node forms a strong coordination bond with the oxygen atom of the rhenium acid radical, and the sulfonic acid group provides an ion exchange site, and the -SO3H group is partially protonated to -SO3 - H + , can adsorb rhenium acid radicals through an ion exchange mechanism, and the rhenium acid radicals captured by the sulfonic acid group can further form a stronger coordination bond with Zr 4+ , to realize efficient adsorption of rhenium. DETAILED DESCRIPTION

[0036] The present application will be described in detail below through specific embodiments, and those skilled in the art can understand that the specific embodiments below are only for illustrative purposes, and do not limit the scope of the present application in any way. In addition, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If the specific processing conditions and methods are not explicitly described in the following embodiments, the conditions and methods known in the art can be used for processing.

[0037] In one aspect, the present application provides a preparation method of a core-shell structure MOF material for selectively adsorbing rhenium, comprising the following steps:

[0038] (1) mixing UiO-66-SO3H and a template solution, dispersing to obtain a dispersion liquid,

[0039] (2) mixing the dispersion liquid with ammonia water, then adding silicate dropwise to carry out hydrolysis and condensation reaction to obtain SiO2-coated UiO-66-SO3H, denoted as UiO-66-SO3H@SiO2,

[0040] (3) dispersing the UiO-66-SO3H@SiO2 in a polyethyleneimine solution to carry out grafting reaction to obtain a core-shell structure MOF material, denoted as UiO-66-SO3H@SiO2-PEI.

[0041] In the present application, by mixing UiO-66-SO3H and a template solution, dispersing, the template can form a layer of micelles on the surface of UiO-66-SO3H, after adding ammonia water and silicate, the silicate is hydrolyzed and condensed under the catalysis of ammonia water, and the silica is deposited on the surface of UiO-66-SO3H and the template, and then the grafting reaction is carried out in the polyethyleneimine solution, the primary amino group of polyethyleneimine condenses with the silicon hydroxyl group on the silica to form Si-N bond, thereby grafting PEI on the silica.

[0042] In some embodiments of the present application, the UiO-66-SO3H is prepared by a method comprising the following steps:

[0043] mixing a zirconium source, a sulfonic acid functionalized ligand, N,N-dimethylformamide and an acid, ultrasonicating for 8-20 min, then carrying out a solvothermal reaction, and carrying out solid-liquid separation on the obtained reaction liquid to obtain a UiO-66-SO3H precursor,

[0044] washing the UiO-66-SO3H precursor with N,N-dimethylformamide, ethanol and water in sequence, and then drying to obtain UiO-66-SO3H.

[0045] In some embodiments of the present application, the zirconium source is at least one of ZrCl4, ZrOCl4 and Zr(NO3)4, the sulfonic acid functionalized ligand is at least one of 2-sulfonic terephthalic acid and 2-sulfonic sodium terephthalate, and the acid is at least one of glacial acetic acid, formic acid and benzoic acid.

[0046] In some embodiments of the present application, the molar ratio of the zirconium source and the sulfonic acid functionalized ligand is 1:0.8-1.2, specifically 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, etc., the ratio of the zirconium source and N,N-dimethylformamide is 1 mmol: 45-55 mL, specifically 1 mmol: 45 mL, 1 mmol: 50 mL, 1 mmol: 55 mL, etc., and the ratio of N,N-dimethylformamide and the acid is 50 mL: 0.17-0.23 mL, specifically 50 mL: 0.172 mL, 50 mL: 0.18 mL, 50 mL: 0.229 mL, 50 mL: 0.23 mL, etc.

[0047] In some embodiments of the present application, the zirconium source, the sulfonic acid functionalized ligand, N,N-dimethylformamide and the acid are mixed, and the ultrasonic treatment time is specifically 8 min, 10 min, 15 min, 20 min, etc. The ultrasonic treatment can make the raw materials uniformly mixed, facilitating the subsequent solvothermal reaction.

[0048] In some embodiments of the present application, the solvothermal reaction is performed at 115-125℃ for 22-26 h. The present application does not have a special limitation on the container for the solvothermal reaction, and a conventional container can be used. In the embodiments of the present application, the solvothermal reaction is performed in a closed reaction kettle. The temperature of the solvothermal reaction is 115-125℃, specifically 115℃, 120℃, 125℃, etc. The time of the solvothermal reaction is 22-26 h, specifically 22 h, 24 h, 26 h, etc.

[0049] In some embodiments of the present application, the temperature of the N,N-dimethylformamide, ethanol and water used for washing is 50-60℃, specifically 50℃, 55℃, 60℃, etc. In the present application, the use of preheated washing liquid can effectively dissolve and wash away the residual solvent and unreacted ligand. The surface tension of the preheated washing liquid is low, which is conducive to maintaining the pore structure of the MOF and preventing the collapse of the pores.

[0050] In some embodiments of the present application, the UiO-66-SO3H precursor is dried by freeze-drying after being washed with N,N-dimethylformamide, ethanol and water in turn; in the embodiments of the present application, the temperature of freeze-drying is -50°C, the pressure is 10 Pa, and the time is 24 h.

[0051] In some embodiments of the present application, the template agent in the template agent solution is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and octadecyltrimethylammonium bromide; the solvent in the template agent solution is ethanol; the concentration of the template agent solution is 0.25-0.35 mol / L, and specifically can be 0.25 mol / L, 0.30 mol / L or 0.35 mol / L; and the ratio of the UiO-66-SO3H to the template agent solution is 100 mg:45-60 mL, and specifically can be 100 mg:45 mL, 100 mg:50 mL, 100 mg:55 mL or 100 mg:60 mL.

[0052] After obtaining the dispersion, the dispersion is mixed with ammonia water, and then silicon ester is added dropwise to perform hydrolysis and condensation reaction to obtain SiO2-coated UiO-66-SO3H, denoted as UiO-66-SO3H@SiO2.

[0053] In some embodiments of the present application, the concentration of the ammonia water is 0.4-0.7 wt%, and specifically can be 0.4 wt%, 0.5 wt%, 0.6 wt% or 0.7 wt%; and the ratio of the UiO-66-SO3H to the ammonia water is 100 mg:0.15-0.3 mL, and specifically can be 100 mg:0.15 mL, 100 mg:0.2 mL, 100 mg:0.25 mL or 100 mg:0.3 mL. In the present application, the above-mentioned concentration of ammonia water is moderate, which can ensure the formation of a completely coated shell at a relatively high reaction rate, while a too high concentration leads to a fast reaction rate, which may result in the disordered accumulation of SiO2 and uneven distribution of the shell, and a too low concentration leads to insufficient catalyst, which may result in incomplete coating of the shell.

[0054] In some embodiments of the present application, the silicon ester is tetraethyl orthosilicate, and the ratio of the UiO-66-SO3H to the silicon ester is 100 mg:0.08-0.12 mL, and specifically can be 100 mg:0.08 mL, 100 mg:0.10 mL or 100 mg:0.12 mL. In the present application, the above-mentioned range further ensures complete coating of the shell, while below the above-mentioned range, the SiO2 shell is too thin or discontinuous to form a complete coating, and above the above-mentioned range, the shell is too thick to easily block the MOF pores.

[0055] In some embodiments of the present application, the temperature of the hydrolysis condensation reaction is 10-20℃, which can be specifically 10℃, 15℃, 20℃, etc.; the time of the hydrolysis condensation reaction is 22-26 h, which can be specifically 22 h, 23 h, 24 h, 25 h, 26 h, etc.; the hydrolysis condensation process is kept in a stirring state. In the present application, the template agent forms micelles in the solution, and the silica is uniformly attached to the template during the hydrolysis condensation reaction to form uniform pores; and by further controlling the concentration of the template agent and the hydrolysis condensation conditions during the hydrolysis condensation process, the pore size of the shell layer can be further controlled to be 0.5-0.8 nm, so as to avoid the sulfate, molybdate and arsenate from entering the material as much as possible.

[0056] In some embodiments of the present application, after the hydrolysis condensation reaction is completed, the obtained reaction solution is further subjected to solid-liquid separation to obtain a crude product of UiO-66-SO3H@SiO2, and the crude product of UiO-66-SO3H@SiO2 is sequentially washed with 1% hydrochloric acid / ethanol solution and 0.1M sodium bicarbonate aqueous solution to obtain UiO-66-SO3H@SiO2. In the present application, the unreacted template agent can be removed by washing with 1% hydrochloric acid / ethanol solution (obtained by mixing 1 part of concentrated hydrochloric acid with a concentration of 37 wt% and 36 parts of ethanol), and the residual hydrochloric acid can be neutralized by washing with 0.1M sodium bicarbonate solution, so as to avoid the protonation of the amino group of polyethyleneimine (PEI), resulting in a decrease in the grafting rate, and avoid the protonated PEI from being combined with the surface of SiO2 by electrostatic interaction, resulting in the shell layer being easy to fall off. The number of times of washing in the present application is not particularly limited, and the purpose of removing the template agent and neutralizing the hydrochloric acid can be achieved; in the examples of the present application, the number of times of washing is 3.

[0057] In the present application, the specific method of solid-liquid separation is not particularly limited, and the solid and liquid can be separated; in the examples of the present application, the method of solid-liquid separation is centrifugal separation.

[0058] After obtaining UiO-66-SO3H@SiO2, the UiO-66-SO3H@SiO2 is dispersed in a polyethyleneimine solution to perform a grafting reaction, so as to obtain a core-shell structure MOF material, which is denoted as UiO-66-SO3H@SiO2-PEI.

[0059] In some embodiments of the present application, the solvent of the polyethyleneimine solution is ethanol; the molecular weight of the polyethyleneimine is 600-1200, specifically 600, 800, 1200, etc.; the concentration of the polyethyleneimine solution is 1.5-2.5 wt / v%, specifically 1.5 wt / v%, 2.0 wt / v%, 2.5 wt / v%, etc.; the mass ratio of polyethyleneimine in the polyethyleneimine solution to silicon in tetraethyl orthosilicate is 3:6-8, specifically 3:6, 3:7, 3:8, etc.

[0060] In some embodiments of the present application, the grafting reaction is carried out under reflux conditions; the temperature of the grafting reaction is 65-75℃, specifically 65℃, 70℃, 75℃, etc.; specifically, the time of the grafting reaction is 3.5-4.5 h, specifically 3.5 h, 4.0 h, 4.5 h, etc.

[0061] In some embodiments of the present application, after the completion of the grafting reaction, the reaction solution obtained by the grafting reaction is further subjected to solid-liquid separation to obtain a crude UiO-66-SO3H@SiO2-PEI, and the crude UiO-66-SO3H@SiO2-PEI is sequentially washed with ethanol, subjected to tert-butyl alcohol solvent replacement, and dried to obtain UiO-66-SO3H@SiO2-PEI. In the present application, the unreacted polyethyleneimine can be removed by ethanol washing, and the purpose of pore preservation can be achieved by tert-butyl alcohol solvent replacement; specifically, if tert-butyl alcohol solvent replacement is not performed, the ethanol will generate a huge capillary force during the drying process, which may cause the collapse of the pore structure and cannot preserve the pores, while the surface tension of tert-butyl alcohol is low, the capillary force is lower than that of ethanol, and the freezing point is 25.5℃, which directly sublimates from solid to gas during freeze-drying without generating a gas-liquid interface, eliminating the capillary force, thus achieving the purpose of pore preservation after tert-butyl alcohol solvent replacement. The number of ethanol washing in the present application is not particularly limited, and in the examples of the present application, the number of ethanol washing is 3 times; the method of tert-butyl alcohol solvent replacement in the present application is not particularly limited, as long as the purpose of tert-butyl alcohol solvent replacement can be achieved, and in the examples of the present application, tert-butyl alcohol is used for soaking, the soaking time is 10 min each time, and the number of tert-butyl alcohol solvent replacement is 3 times.

[0062] Another aspect of the present application also provides a preparation method of a rhenium adsorption material, comprising the following steps:

[0063] The selective rhenium adsorption core-shell structure MOF material obtained by the preparation method of any one of the preceding technical solutions, polyvinylidene fluoride, and an organic solvent are mixed to obtain an extrusion material,

[0064] The extrusion material is extruded and then cut to obtain a rhenium adsorption material precursor,

[0065] The rhenium adsorption material precursor is dried after ethanol replacement to obtain a rhenium adsorption material.

[0066] In the present application, the core-shell structure MOF material selectively adsorbing rhenium is in a powder structure, which is directly applied in industry and is easy to lose. In the present application, polyvinylidene fluoride is used as a binder to bond the core-shell structure MOF material selectively adsorbing rhenium together to form a large-particle rhenium adsorption material to meet the needs of industrial application.

[0067] The core-shell structure MOF material selectively adsorbing rhenium, polyvinylidene fluoride and an organic solvent are mixed to obtain an extrusion material.

[0068] In some embodiments of the present application, the mass ratio of the core-shell structure MOF material selectively adsorbing rhenium and polyvinylidene fluoride is 1:0.4-0.6, and specifically can be 1:0.4, 1:0.5, 1:0.6, etc.; the ratio of the core-shell structure MOF material selectively adsorbing rhenium and the organic solvent is 3.0 g: 6-8 mL, and specifically can be 3.0 g: 6 mL, 3.0 g: 7 mL, 3.0 g: 8 mL, etc. In the present application, the above ratio can ensure that the obtained extrusion material is in a dough shape, so as to be able to be used for subsequent extrusion operation; at the same time, it also ensures that the obtained rhenium adsorption material has excellent selective adsorption.

[0069] In some embodiments of the present application, the organic solvent is N-methyl pyrrolidone.

[0070] After obtaining the extrusion material, the extrusion material is extruded, and then cut to obtain a rhenium adsorption material precursor.

[0071] In some embodiments of the present application, the rhenium adsorption material precursor is a columnar particle, the diameter of which is 1.5-2.5 mm, and specifically can be 1.5 mm, 2.0 mm, 2.5 mm, etc.; the length of which is 2-4 mm, and specifically can be 2 mm, 3 mm, 4 mm, etc.

[0072] After obtaining the rhenium adsorption material precursor, the rhenium adsorption material precursor is dried after ethanol replacement to obtain a rhenium adsorption material.

[0073] In some embodiments of the present application, the ethanol replacement comprises the following steps: soaking the rhenium adsorption material precursor in a mixed solution of ethanol and N-methylpyrrolidone with a volume ratio of 3:7 for 0.8-1.2 h (for example, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, etc.), then soaking in 60 v / v% ethanol aqueous solution for 0.8-1.2 h (for example, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, etc.), and then soaking in ethanol for 0.8-1.2 h (for example, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, etc.).

[0074] Another aspect of the present application also provides the use of the rhenium adsorption material prepared by the preparation method of any one of the above technical solutions in the recovery of rhenium from waste acid.

[0075] The present application does not have special limitations on the water quality of the waste acid, and preferably the waste acid is filtered and has no suspended matter; in the embodiments of the present application, the pH of the waste acid is 1.5-3.0, the sulfate concentration is ≤200 g / L, the fluoride ion is ≤500 mg / L, and the temperature is 20-60℃.

[0076] The person skilled in the art can select how to use the rhenium adsorption material according to the specific waste acid to be treated. In the embodiments of the present application, the rhenium adsorption material is put into the waste acid, adsorption is carried out, and then the rhenium adsorption material is filtered out to achieve the purpose of removing rhenium.

[0077] The technical solutions in the present application will be described clearly and completely below in combination with the embodiments. The embodiments of the present application are only examples, and all other embodiments obtained by the person skilled in the art without creative labor are within the scope of protection of the present application.

[0078] Example 1

[0079] (1) 2.33 g of ZrCl4, 2.14 g of 2-sulfonic acid terephthalic acid monosodium, 500 mL of N,N-dimethylformamide (DMF), and 1.72 mL of glacial acetic acid were blended, ultrasonically treated for 10 min, and then transferred to a reaction kettle for hydrolysis and condensation reaction at 120℃ for 24 h. After the reaction was completed, the obtained reaction liquid was cooled to room temperature, and then centrifuged to obtain a UiO-66-SO3H precursor. The UiO-66-SO3H precursor was washed with 60℃ DMF, anhydrous ethanol, and pure water for 3 times, and then freeze-dried at-50℃ and 10 Pa for 24 h to obtain UiO-66-SO3H.

[0080] (2) 2.0 g UiO-66-SO3H was added into 1000 mL of a mixture of cetyltrimethylammonium bromide and ethanol with a concentration of 0.3 mol / L, and ultrasonic dispersion was performed for 30 min to obtain a dispersion liquid. 3.0 mL of dilute ammonia water with a concentration of 0.5% was added into the dispersion liquid, 2 mL of tetraethyl orthosilicate was added dropwise, the obtained mixture was stirred at 15 ℃ for 24 h, and then centrifugal separation was performed to obtain a precipitate, which was UiO-66-SO3H@SiO2 crude product. The UiO-66-SO3H@SiO2 crude product was washed with 1% hydrochloric acid / ethanol solution for 3 times, and then rinsed with 0.1 M sodium bicarbonate solution for 1 time to obtain UiO-66-SO3H@SiO2. The UiO-66-SO3H@SiO2 was dispersed in a mixture of 2% polyethyleneimine (107 mg, molecular weight 600) and ethanol, and refluxed at 70 ℃ for 4 h. Then, centrifugal separation was performed on the obtained reaction liquid to obtain a precipitate, which was UiO-66-SO3H@SiO2-PEI crude product. The UiO-66-SO3H@SiO2-PEI crude product was washed with anhydrous ethanol for 3 times, and then soaked in tert-butyl alcohol for 3 times, each time for 10 min. Finally, freeze-drying was performed on the UiO-66-SO3H@SiO2-PEI crude product at-50 ℃ and 10 Pa for 24 h to obtain UiO-66-SO3H@SiO2-PEI, that is, a core-shell structured MOF material.

[0081] (3) 2.0 g of the core-shell structured MOF material, 1.0 g of polyvinylidene fluoride, and 4.7 mL of N-methyl pyrrolidone (NMP) were blended to obtain a dough-like extrusion material. The extrusion material was extruded and cut to obtain columnar particles with a diameter of 2 mm and a length of 3 mm, that is, a rhenium adsorption material precursor. The rhenium adsorption material precursor was soaked in a mixture of anhydrous ethanol and NMP (volume ratio 3:7) for 1 h, then soaked in a 60% ethanol solution for 1 h, and then soaked in anhydrous ethanol for 1 h. Then, the rhenium adsorption material precursor was placed in a vacuum drying oven at 60 ℃ for 24 h to obtain a rhenium adsorption material.

[0082] Example 2

[0083] (1) 2.33 g of ZrCl4, 2.68 g of 2-sulfonic acid terephthalic acid monosodium, 500 mL of N,N-dimethylformamide (DMF), and 1.72 mL of glacial acetic acid were blended, ultrasonic dispersion was performed for 10 min, and then the mixture was transferred into a reaction kettle for hydrolysis and condensation reaction at 120 ℃ for 24 h. After the reaction was completed, the obtained reaction liquid was cooled to room temperature, and then centrifugal separation was performed to obtain a UiO-66-SO3H precursor. The UiO-66-SO3H precursor was washed with 60 ℃ DMF, anhydrous ethanol, and pure water for 3 times, respectively, and then freeze-drying was performed on the UiO-66-SO3H precursor at-50 ℃ and 10 Pa for 24 h to obtain UiO-66-SO3H.

[0084] (2) 2.0 g of UiO-66-SO3H was added into 1000 mL of a mixture of cetyltrimethylammonium bromide and ethanol with a concentration of 0.3 mol / L, and ultrasonic dispersion was performed for 30 min to obtain a dispersion liquid. 3.0 mL of dilute ammonia water with a concentration of 0.5% was added into the dispersion liquid, 2 mL of tetraethyl orthosilicate was added dropwise, and the obtained mixture was stirred at 15°C for 24 h, and then centrifugal separation was performed to obtain a precipitate, which was UiO-66-SO3H@SiO2 crude product. The UiO-66-SO3H@SiO2 crude product was washed with 1% hydrochloric acid / ethanol solution for 3 times, and then rinsed with 0.1 M sodium bicarbonate solution for 1 time to obtain UiO-66-SO3H@SiO2. The UiO-66-SO3H@SiO2 was dispersed in a mixture of 2% polyethyleneimine (107 mg, molecular weight 800) and ethanol, and refluxed at 70°C for 4 h, and then the obtained reaction liquid was centrifugally separated to obtain a precipitate, which was UiO-66-SO3H@SiO2-PEI crude product. The UiO-66-SO3H@SiO2-PEI crude product was washed with anhydrous ethanol for 3 times, and then soaked in tert-butyl alcohol for 3 times, each time for 10 min, and finally freeze-dried at-50°C and 10 Pa for 24 h to obtain UiO-66-SO3H@SiO2-PEI, that is, a core-shell structure MOF material.

[0085] (3) The rhenium adsorption material was prepared according to the method of step (3) of Example 1.

[0086] Example 3

[0087] (1) 2.33 g of ZrCl4, 3.22 g of 2-sulfonic acid p-phthalic acid monosodium, 500 mL of N,N-dimethylformamide (DMF), and 2.29 mL of glacial acetic acid were blended, ultrasonic dispersion was performed for 10 min, and then transferred to a reaction kettle, and hydrolysis and condensation reaction was performed at 120°C for 24 h. After the reaction was completed, the obtained reaction liquid was cooled to room temperature, and then centrifugally separated to obtain a UiO-66-SO3H precursor. The UiO-66-SO3H precursor was washed with 60°C DMF, anhydrous ethanol, and pure water for 3 times, and then freeze-dried at-50°C and 10 Pa for 24 h to obtain UiO-66-SO3H.

[0088] (2) 2.0 g of UiO-66-SO3H was added into 1000 mL of a mixture of cetyltrimethylammonium bromide and ethanol with a concentration of 0.3 mol / L, and ultrasonic dispersion was performed for 30 min to obtain a dispersion liquid. 6.0 mL of dilute ammonia water with a concentration of 0.5% was added into the dispersion liquid, 2 mL of tetraethyl orthosilicate was added dropwise, and the obtained mixture was stirred at 15°C for 24 h, and then centrifugal separation was performed to obtain a precipitate, which was UiO-66-SO3H@SiO2 crude product. The UiO-66-SO3H@SiO2 crude product was washed with 1% hydrochloric acid / ethanol solution for 3 times, and then rinsed with 0.1 M sodium bicarbonate solution for 1 time to obtain UiO-66-SO3H@SiO2. The UiO-66-SO3H@SiO2 was dispersed in a mixture of 2% polyethyleneimine (107 mg, molecular weight 1200) and ethanol, and refluxed at 70°C for 4 h, and then the obtained reaction liquid was centrifugally separated to obtain a precipitate, which was UiO-66-SO3H@SiO2-PEI crude product. The UiO-66-SO3H@SiO2-PEI crude product was washed with anhydrous ethanol for 3 times, and then soaked in tert-butyl alcohol for 3 times, each time for 10 min, and finally freeze-dried at -50°C and 10 Pa for 24 h to obtain UiO-66-SO3H@SiO2-PEI, that is, a core-shell structure MOF material.

[0089] (3) The rhenium adsorption material was prepared according to the method of step (3) of Example 1.

[0090] Comparative Example 1

[0091] The rhenium adsorption material was prepared according to the method of Example 1, wherein step (2) was omitted, and the UiO-66-SO3H obtained in step was used to replace the core-shell structure MOF material in step (3).

[0092] Comparative Example 2

[0093] The granular activated carbon purchased from the State Pharmaceutical Group was used as the rhenium adsorption material.

[0094] Comparative Example 3

[0095] The 717 anion resin purchased from the State Pharmaceutical Group was used as the rhenium adsorption material.

[0096] The simulated waste acid solution was prepared according to the following proportions: rhenium 19.4 mg / L, sulfate 150 g / L, and pH 2.1 in an aqueous solution, which was prepared from ammonium perrhenate and sulfuric acid, specifically, 85 mL of concentrated sulfuric acid was slowly added to 900 mL of deionized water under ice water bath stirring, and after cooling to room temperature, 68.2 mL of ammonium perrhenate stock solution with a concentration of 284.5 mg / L (calculated as rhenium) was added, and then transferred to a 1000 mL volumetric flask and diluted with deionized water.

[0097] The rhenium adsorption material was added to the simulated waste acid solution at a concentration of 1 g / L, and oscillated at room temperature for 24 h, and then the ion concentration in the solution was tested by inductively coupled plasma optical emission spectrometry (ICP-OES). The adsorption rates of sulfate and rhenium were calculated. The results are shown in Table 1.

[0098] Table 1 Test results of adsorption rates of ions in simulated waste acid and actual waste acid

[0099]

[0100] As can be seen from Table 1, the adsorption rates of rhenium adsorption materials obtained in Examples 1-3 to rhenium are all higher than 95%, and the adsorption rate of Comparative Example 1 is 71.1%, indicating that the shell promotes the selective adsorption of rhenium, and the external shell blocks the interference ions through ion sieving effect; the activated carbon of Comparative Example 2 has no specific adsorption, which may be because the pores are saturated with sulfate, and the adsorption rate of rhenium is low; the anion resin of Comparative Example 3 has a certain adsorption to rhenium, but the adsorption rate of rhenium is low due to the competition of sulfate for ion exchange sites.

[0101] The actual waste acid of a certain smelting enterprise was used as the treatment object, and a filter was used to filter to remove impurities and colloids, and the filtered waste acid was treated, wherein the concentrations of various substances were as follows: rhenium 19.4 mg / L, arsenic 3.9 g / L, sulfate 150 g / L, molybdenum 13.2 mg / L, fluorine 208 mg / L, and pH 2.1. The adsorption rate of rhenium was tested by the foregoing method, and after each test, the rhenium adsorption material was eluted (the rhenium adsorption material saturated with adsorption was filtered out, and a small amount of deionized water was used for rapid rinsing to remove the residual waste acid on the surface, and then immersed in 1.0 mol / L ammonia water solution, oscillated at 150 rpm at 25°C for 2 hours for elution, after elution, the material was separated by filtration, washed with deionized water until the effluent was neutral, and finally the material was dried in a vacuum drying oven at 60°C for 4 hours, and regeneration was completed), and then the foregoing rhenium adsorption process was repeated again to test its stability, and a total of 10 times of tests were performed, i.e. 10 times of cycle stability were tested. The results are shown in Table 2.

[0102] Table 2 Adsorption effect of rhenium adsorption materials obtained in Examples 1-3 after 10 cycles

[0103]

[0104] As can be seen from the data in Table 2, the adsorption rates of the rhenium adsorption materials obtained in Examples 1-3 to rhenate are all higher than 90%, the adsorption rate of sulfate is lower than 1%, the adsorption rate of arsenate is lower than 5%, and the adsorption rate of molybdate is lower than 40%, indicating that the rhenium adsorption material provided by the present application has good adsorption effect and selectivity to rhenate. After 10 cycles, the adsorption rate to rhenate slightly decreases, and the attenuation rate is lower than 1.7%, indicating that the rhenium adsorption material prepared by the method has good stability.

[0105] While the preferred embodiments of the application have been illustrated and described, it will be clear to those skilled in the art that various changes can be made without departing from the spirit and scope of the application, which is defined by the appended claims.

Claims

1. A method for preparing a core-shell structured MOF material that selectively adsorbs rhenium, comprising the following steps: (1) Mix UiO-66-SO3H and template agent solution, and disperse to obtain a dispersion. (2) The dispersion was mixed with ammonia water, and then silicate ester was added dropwise to carry out a hydrolysis-condensation reaction to obtain SiO2-coated UiO-66-SO3H, denoted as UiO-66-SO3H@SiO2. (3) Disperse the UiO-66-SO3H@SiO2 in a polyethyleneimine solution and carry out a grafting reaction to obtain a core-shell structured MOF material, denoted as UiO-66-SO3H@SiO2-PEI; After the hydrolysis and condensation reaction is completed, the reaction solution is further subjected to solid-liquid separation to obtain crude UiO-66-SO3H@SiO2. The crude UiO-66-SO3H@SiO2 is washed sequentially with 1 wt% hydrochloric acid / ethanol solution and 0.1 M sodium bicarbonate aqueous solution to obtain UiO-66-SO3H@SiO2. After the grafting reaction is completed, the reaction solution obtained from the grafting reaction is subjected to solid-liquid separation to obtain crude UiO-66-SO3H@SiO2-PEI. The crude UiO-66-SO3H@SiO2-PEI is then washed with ethanol, replaced with tert-butanol solvent, and dried to obtain UiO-66-SO3H@SiO2-PEI.

2. The preparation method according to claim 1, characterized in that, The UiO-66-SO3H is prepared by a method including the following steps: A zirconium source, a sulfonic acid-functionalized ligand, N,N-dimethylformamide, and an acid were mixed and sonicated for 8-20 min, followed by a solvothermal reaction. The resulting reaction solution was then subjected to solid-liquid separation to obtain the UiO-66-SO3H precursor. The UiO-66-SO3H precursor was washed sequentially with N,N-dimethylformamide, ethanol and water, and then dried to obtain UiO-66-SO3H.

3. The preparation method according to claim 2, characterized in that, The zirconium source is at least one of ZrCl4 and Zr(NO3)4, the sulfonic acid-functionalized ligand is at least one of 2-sulfonic acid terephthalic acid and sodium 2-sulfonic acid terephthalate, and the acid is at least one of glacial acetic acid, formic acid, and benzoic acid. The molar ratio of the zirconium source to the sulfonic acid-functionalized ligand is 1:0.8-1.2, the ratio of the zirconium source to N,N-dimethylformamide is 1 mmol:45-55 mL, and the ratio of N,N-dimethylformamide to acid is 50 mL:0.17-0.23 mL. The solvothermal reaction was carried out at 115-125℃ for 22-26 h. The temperature of the N,N-dimethylformamide, ethanol, and water used in the washing process is 50-60°C. The drying process is freeze-drying.

4. The preparation method according to claim 1, characterized in that, The template agent in the template solution is at least one selected from hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and octadecyltrimethylammonium bromide. The solvent in the template agent solution is ethanol. The concentration of the template agent solution is 0.25-0.35 mol / L. The ratio of UiO-66-SO3H to the template agent solution is 100 mg: 45-60 mL. The concentration of the ammonia water is 0.4-0.7 wt%, and the ratio of UiO-66-SO3H to ammonia water is 100 mg: 0.15-0.3 mL. The silicate ester is tetraethyl orthosilicate, and the ratio of UiO-66-SO3H to the silicate ester is 100 mg: 0.08-0.12 mL. The hydrolysis-condensation reaction is carried out at a temperature of 10-20℃ for 22-26 hours, and is kept under stirring during the process.

5. The preparation method according to claim 1, characterized in that, The solvent for the polyethyleneimine solution is ethanol, the concentration of the polyethyleneimine solution is 1.5-2.5 wt / v%, the mass ratio of polyethyleneimine to silicon in the silicate ester is 3:6-8, and the molecular weight of the polyethyleneimine is 600-1600. The grafting reaction is carried out under reflux conditions, the temperature of the grafting reaction is 65-75℃, and the time of the grafting reaction is 3.5-4.5 h.

6. A method for preparing a rhenium adsorbent material, comprising the following steps: The selectively rhenium-adsorbing core-shell MOF material prepared by the preparation method according to any one of claims 1-5, polyvinylidene fluoride, and an organic solvent are mixed to obtain an extruded material. The extruded material is extruded and then cut to obtain a rhenium adsorbent material precursor. The rhenium adsorbent precursor was replaced with ethanol and then dried to obtain the rhenium adsorbent material.

7. The preparation method according to claim 6, characterized in that, The mass ratio of the core-shell MOF material selectively adsorbing rhenium to polyvinylidene fluoride is 1:0.4-0.6, and the ratio of the core-shell MOF material selectively adsorbing rhenium to organic solvent is 3.0 g:6-8 mL. The organic solvent is N-methylpyrrolidone. The rhenium adsorbent precursor is a columnar particle with a diameter of 1.5-2.5 mm and a length of 2-4 mm.

8. The preparation method according to claim 7, characterized in that, The ethanol replacement includes the following steps: soaking the rhenium adsorbent precursor in a mixed solution of ethanol and N-methylpyrrolidone in a volume ratio of 3:7 for 0.8-1.2 h, then soaking it in a 60 v / v% ethanol aqueous solution for 0.8-1.2 h, and then soaking it in ethanol for 0.8-1.2 h.

9. The application of a rhenium adsorbent material prepared by any one of claims 6-8 for recovering rhenium from waste acid.

Citation Information

Patent Citations

  • Method for recycling rhenium from copper smelting acidic wastewater

    CN110468277A

  • Method for preparing 4N ammonium rhenate from low-concentration rhenium-containing waste acid

    CN116715274A

  • Method for multi-stage concentration and purification of ammonium rhenate from ammonium rhenate strip liquor

    CN117682561A

  • Aminated magnetic UiO-66 preparation method

    CN109232907A

  • Functionalized magnetic MOF composite nano-material, and preparation and nuclear industrial application thereof

    CN111375386A